CONTEXTUALIZATION OF THE MEANING OF KAFA>'AH IN QS. AN-NUR [24]: 26 - Faiqoh Naufalia Arrozi; Abu Bakar (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
Kafa>‘ah in Islamic law is the compatibility between men and women. Although it is not included in the valid requirements of marriage, it is important to pay attention to the concept of kafa>‘ah, which in this case is implicitly mentioned in the Qur'an. One of them is QS. An-Nur verse 26. It implies that a good woman will get a good man, and vice versa. This will be connected with what often happens among the habaib. Sharifah is not allowed to marry a non Sayyid. Kafa>ah how is meant in the verse when associated with this modern era. So this study will be studied about how the contextual meaning of QS. An-Nur verse 26 uses Abdullah Saeed's contextual interpretation. This type of research is library research (literature) and uses descriptive-analytical methods. It starts by explaining the meaning of kafa>‘ah, Abdullah Saeed's contextual interpretation theory, and applying the contextual theory to. This research reviews the meaning of kafa>‘ah in QS. An-Nur verse 26 with Abdullah Saeed's contextual approach. The results show that kafa>‘ah in marriage does not only include aspects of nasab, religion, morals, wealth, and position but also takes into account the feelings between partners. This allows them to understand, support, and appreciate each other in all aspects of life, facing trials and challenges together.